(3HOjYjI YR GdOjf GdehUdjs - (3GdehUdj, YR GdOjf, Ydj Hf GdMSjf Hf Ydj, J(B789(3g`s
(3ChdgG (B:s
(3HQGYI JSJgd GdOeY aj GdYde (B*** (3YHGQI JSJgd GdOeY aj GdYde , Mj Sdei hSd eG QcHJ HTQG (B*** (3bO CWdbJg CeGe GdMj Yf Cees
(3BNQgG (B:s
(3MWJ eSGhGI eYfGg hUhQJg (B*** (3aj GdMSf TGgOI aj fhf hGdbde , aGLYd dg eNdUG ef bHM RdJg (B*** (3aj MSf eaJJM efg heNJJejs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 280s
(3eYLe GdeDdajf(B: 2 / 431s
(3cTa GdXfhf(B: 1 / 173s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs